The Antithrombotic Potential of Tinzaparin and Enoxaparin Upon Thrombin Generation Triggered In Vitro by Human Ovarian Cancer Cells IGROV1. (March 2017) - Sassi, Mouna; Chakroun, Taher; Mbemba, Elisabeth; Van Dreden, Patrick; Elalamy, Ismail; Larsen, Annette K.; Gerotziafas, Grigoris T.
Background: A documented relationship between ovarian cancer and thrombosis does exist. Low-molecular-weight heparins (LMWHs) are cornerstone drugs in the primary prevention and treatment of venous thromboembolic events in patients with cancer. However, cancer cells may alter the efficiency of these antithrombotic agents. Objective: We aimed to characterize the procoagulant phenotype of human epithelial ovarian adenocarcinoma cells, IGROV1, and to compare the capacity of tinzaparin and enoxaparin to inhibit thrombin generation triggered by these cells. Methods: Thrombin generation induced by different concentrations of IGROV1 cells on platelet poor plasma (PPP) was assessed by the calibrated automated thrombogram assay. Tissue factor (TF) expression was studied using Western blot analysis. Then, the experimental model of thrombin generation was used to compare the inhibitory effect of clinically relevant concentrations of both tinzaparin and enoxaparin. The inhibitory concentration 50 (IC50) of the mean rate index and the endogenous thrombin potential and the 2-fold increase in lag time were analyzed on the basis of the anti-Xa and anti-IIa activities of the LMWHs. Results: IGROV1 cells suspended into PPP resulted in a significant increase in thrombin generation in the absence of any exogenous source of TF and phospholipids. Tissue factor was expressed by IGROV1 cells. Tinzaparin was a more potent inhibitor of thrombin generation than enoxaparin. The inhibition of thrombin generation induced by IGROV1 cancer cells depended mainly on the anti-Xa activity of the LMWHs. Conclusion: This experimental study in ovarian cancer cells demonstrates that the antithrombotic activity of LMWHs is not completely predicted by the anti-Xa or anti-IIa activities measured in PPP.